Reassessing the approach to jurisdiction in civil and commercial matters: Party autonomy, categorical equality and sovereignty - KARAYANIDI, MILANA (Trinity College Dublin. School of Law. Discipline of Law, 2018)
The subject of conflict of laws and the topic of judicial jurisdiction in particular are not often theorised about. This work aims to contribute to the scholarship in the area by offering a revised look on values behind a jurisdiction regime. The findings demonstrate that re-conceptualisation of justification for judicial jurisdiction is needed. Rather than deriving from the territorial power of the states, determination of jurisdiction in international matters ought to be driven by party autonomy. The general rule of party autonomy can be limited by considerations of categorical equality (in view of protecting certain categories of private parties) and sovereignty (limited state sovereign interests essential to preserve the integrity of the international system). This thesis developed from observing the existing rules on judicial jurisdiction and the case law in Europe and Russia, and evaluating the hypotheses and theories justifying those rules. The method of doctrinal legal analysis was used to examine the primary sources. This method helped identify and classify the legal principles behind the rules. The general analytical method was employed to find insights into the theoretical background of jurisdiction in private international law. This thesis interacted, argued with and sought proof in a number of the scholarly writings on jurisdiction. In addition, the comparative method constituted a significant part of methodology for this thesis. To construct the argument, the legal traditions in private international law of these two regimes were studied: the Brussels jurisdiction regime applicable across the European Union and Russian rules on international jurisdiction in civil and commercial matters. Since Europe constitutes a unique merge of many differing legal principles; the interpretation of the European rules was derived both from the case law of the European Court of Justice (ECJ) and some national case law. The choice of these jurisdictions was predicated by their unique positions towards values in private international law and contrasting societal norms that accommodate those values. Legal training in the English common law and the European law and emergence in the Russian language and culture by origin of the author provided necessary fluency in the target jurisdictions’ regimes. The comparative method helped assess the values and rules prevailing in these legal systems, with an objective ‘to bring about a certain sense of relativity’ to the prevailing views. By discussing the similarities and differences, and the merits of national solutions, ways were sought to improve the existing rules. Finally, the historical method was used to substantiate some parts of this research. As described by the leading founder of the German school of historical law, Savigny, this method presupposes examining the past of legal rules, so as to ‘obtain the mastery over them by a thorough grounding in history’. This method helped trace the origins of the legal concepts and understand certain unusual rules. Therefore, relying on a combination of methods (legal doctrinal analysis, the general analytical method, the comparative and the historical methods), this thesis proposes a fresh view on jurisdiction that can fit the rules of jurisdiction in Europe and Russia in their current form, with certain adjustments.
APPROVED
Keywords: conflict of laws; jurisdiction; private international law